Peminggiran Jemaat Ahmadiyah Indonesia (JAI) dan Penyesuaian Tindakan Sosialnya - Catur Wahyudi (JURNAL INDO-ISLAMIKA, 2015)
This article reveals the marginalization of Jemaat Ahmadiyah Indonesia (JAI) or Qadiyani Ahmadiyah in Indonesia and adjustment of social action, especially during the reign of the reform era. JAI social action adjustment is indicated by aseries of reality, namely: (1) basic solid belief in distress situations though never make existence weakened; (2) the exclusion of that happening is seen as the potential to increase the spirit of congregation more organized, making the movements exist with or without the attributes of the community; (3) the existence of accommodating movement patterns, contributing positively to the stability of the State and to develop humanitarian activities; and (4) their ability to orient its movement through the mechanism of purport back to his faith, sothat open to the more significant accommodating space. Through the process of adjustment of the social action, JAI resilience as an organization has strengthened. This study provides strong support to the theory of inclusive interaction as relational institutions in civil society or order of a civilized society.